2007
DOI: 10.1021/jp072335+
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Templated Ordered Array of Gold Nanorods in One and Two Dimensions

Abstract: Many sensing/catalytic applications in nanotechnology require a programmed assembly of nanospheres/nanorods onto surfaces. The gold nanorods, formed by a seed-mediated, surfactant-assisted synthesis protocol, are stabilized in solution due to surface modification by the surfactant cetyltrimethylammonium bromide. DNAtemplated self-assembly of gold nanorods with different aspect ratios at different DNA concentration values has been studied using transmission electron microscopy. Under appropriate conditions such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 26 publications
3
63
0
Order By: Relevance
“…It is consistent with the previous reports that the longitudinal band of GNRs is more sensitive to the local environment around GNRs than the transverse band [42][43][44][45]. This result suggested that the aggregation of GNRs takes place in a side-by-side manner [46,47].…”
Section: +supporting
confidence: 93%
“…It is consistent with the previous reports that the longitudinal band of GNRs is more sensitive to the local environment around GNRs than the transverse band [42][43][44][45]. This result suggested that the aggregation of GNRs takes place in a side-by-side manner [46,47].…”
Section: +supporting
confidence: 93%
“…Plasmonic Au@Ag nanorods were prepared by using our previous modified method [14,40]. The synthesis procedure is shown in Fig.…”
Section: Preparation and Characterization Of Au@ag Nanorodsmentioning
confidence: 99%
“…12 Given the advanced state of their production, most recent experimental work on gold nanorods has focused on further manipulation of their surface chemistry, [13][14][15][16][17][18][19][20][21][22][23][24] formation of complex assemblies, [25][26][27][28][29][30][31][32][33] and development of biomedical and sensing applications.…”
mentioning
confidence: 99%